Is capsule endoscopy appropriate for elderly patients? The influence of ageing on findings and diagnostic yield: An Italian retrospective study. Issue 12 (December 2015) - Urgesi, Riccardo; Cianci, Rossella; Pagliari, Danilo; Newton, Estelle E.; Rizzo, Gianluca; Costamagna, Guido; Riccioni, Maria Elena
Abstract: Background: Few data are available on the use of capsule endoscopy in the elderly. Methods: We performed a retrospective study on 1008 consecutive patients referred to our centre between December 1, 2002 and January 30, 2014 who underwent capsule endoscopy for various indications. Patients were enrolled and divided into 3 sub-groups according to their age (Group A: <50 years; Group B: 50–69 years; Group C: >70 years). The Pillcam diagnostic yield, clinically significant findings and post-treatment outcomes were compared between groups. Results: Diagnostic yield was significantly higher in Group C vs. Groups A and B (65.2% vs. 42.3% and 47.5%, respectively; p  < 0.05). The most common diagnosis in the elderly was angiodysplasia (42.5%). In 84.5% of elderly patients (Group C) capsule endoscopy results modified patient management. Conclusions: Capsule endoscopy has a high diagnostic yield and positive impact on management in patients aged >70 years.